La dinámica social de Augusto Comte - Popescu, Oreste (1962)
By opposing "dynamics" and "statics" Comte has opened a new chapter in the history of the term "dynamics". In spite of the controversy about the use of the term "dynamics", the terminology introduced by Comte can be very useful to science, as it already proved to be in economics, although conceived in a somewhat different manner. In Comte's sociology the concept "dynamics" has the sense of transformation or, more directly, that of evolution. Comte's social dynamics based on the "law of the three states" (the theologic or fictitious, the metaphysical or abstract and the scientific or positive state), valid in the life of societies as well as in that of individuals. He considers the endogenous as promotive forces of the social process. Nevertheless, whereas some societies have never known primitive stages or have developed through different phases, others have over jumped several degrees of the linear progress or have suffered a delay in their evolution.